(untitled) (Asian Journal of Ethnobiology, 2023)
Abstract. Kilasho A, Kolade MA, Oluborode J, Jackson V, Afolabi S. 2023. Ethnobotanical study of medicinal plants in Ogotun-Ekiti, Ekiti State, Nigeria. Asian J Ethnobiol 6: 138-144. The essential role of medicinal plants in maintaining human health demonstrates the necessity for appropriate knowledge and documentation of their significance and application. The aim of this study is to thoroughly and methodically record the ethnobotanical knowledge of medicinal plants by local community in Ogotun-Ekiti, Nigeria. The data was collected using both interview method and a structured questionnaire. Respondents were chosen based on their experience, related job and deep understanding of the usage of herbal medicines. According to the findings of the research, 81 medicinal plant species from 40 families and 78 genera were identified and documented. The study also revealed that trees make up 58% of all plants, shrubs make up 27%, herbs make up to 10%. Furthermore, leaves (57%) were the most plant parts used in treating several ailments followed by bark (21%), root (10%) and the seeds (8%) as the least used plant parts. Plants from the Malvaceae family (9 species) were recorded to be the most available in the study area, followed by the Fabaceae family (7 species), Moraceae and Asteraceae (each with 5 species) and three species each from Anarcadiaceae, Combreteaceae, Poaceae, Sapotaceae, Curcurbiataceae, Rutaceae, Solanaceae and Lamiaceae. Some of the frequent illnesses treated with medicinal plants in the study region include: malaria, urinary tract infection, diarrhoea, diabetes amongst others. This study concluded that ethnobotanical survey is crucial for assessing current knowledge and serving as a baseline for future analyses of changes in knowledge and usage. These will thereby give the use of medicinal plants more national and global recognition.